Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Konsumen Di Rocket Chicken Dringu Kabupaten Probolinggo - Indah Dwi Oktavia; Ngatimun Ngatimun; Dedi Joko Hermawan (Universitas Panca Marga, 2023)
This research was conducted on Rocket Chicken Dringu, Probolinggo Regency with the aim of knowing the effect of the marketing mix on consumer purchasing decisions at Rocket Chicken Dringu, Probolinggo Regency. The type of research used is quantitative research. The population is all consumers who come to buy products at Rocket Chicken Dringu, Probolinggo Regency and the sample is taken using a non-probability sampling technique through internal sampling (accidental sampling), as many as 50 respondents. Data collection methods used in this study were observation, questionnaires and documentation which were distributed to respondents. Methods of data analysis from research results, namely quantitative methods in the form of validity and reliability tests as well as testing hypotheses with multiple linear regression analysis, determination tests and partial tests, simultaneous and dominant tests using SPSS Version 23.0. The results showed that the Product, Price, Distribution Channel, and Promotion Variables simultaneously or jointly and partially had a significant effect on the dependent variable, namely the Purchase Decision of Rocket Chicken Dringu Products. And Promotion has the most dominant influence on purchasing decisions compared to other variables.